Fiqh Muamalah Review of the Object of Akad (E-Commerce) on Defective Goods - Cut Anggraini; Tri Inda Fadhila Rahma; Atika Atika (UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines the application of Fiqh Muamalah to buying and selling practices in e-commerce, with a focus on the seller's responsibility for defective goods. Using a qualitative method through literature review and normative analysis, the research draws upon scholarly works, journal articles, and relevant Islamic legal sources. The study aims to provide a conceptual framework that aligns Islamic commercial ethics with contemporary online transaction practices. The findings reveal that e-commerce transactions can be considered valid under Fiqh Muamalah if they fulfill essential sharia principles, including justice (‘adl), honesty (ṣidq), and transparency (bayān). The use of Salam and Istishna’ contracts is permissible provided the object of sale is clearly defined, halal, and free from gharar (uncertainty). Furthermore, the study highlights the relevance of khiyār al-‘ayb (option due to defect) and khiyār al-syarth (conditional option) as Islamic legal mechanisms that offer fair resolutions in cases involving defective products. This research supports the growth of sharia-compliant digital commerce by offering practical, jurisprudential solutions and emphasizing key ethical values—trust, accountability, and consumer protection—to promote fair, transparent, and sustainable e-commerce in line with Islamic principles.Keyword: Muamalah Fiqh; Contract Objects; E-Commerce; Defective Goods.